Isolation and Synthesis of Glycophospholipids from the extremophile Chthonomonas calidirosea. Issue 11 (23rd September 2020) - Compton, Benjamin J.; Lagutin, Kirill; Dyer, Blake S.; Ryan, Jason; MacKenzie, Andrew; Stott, Matthew B.; Nekrasov, Eduard V.; Painter, Gavin F.; Vyssotski, Mikhail
Abstract: An interesting set of ten phospholipids including eight previously unreported compounds have been isolated from the extremophile Chthonomonas calidirosea (strain T49 T ). Common within these metabolites is the phosphatidylglyceroylalkylamine core unit with the newly identified compounds containing α‐linked glucosyl, xylosyl or N ‐alanylglucosaminyl monosaccharides. The previously reported N ‐acetylglucosaminyl and aglycone derivatives were also identified in extracts from this bacterium. All metabolites were accompanied by a structural isomer which was shown to contain an extra hydroxyl group within the alkylamine chain. The absolute regio‐ and stereochemistries of the major phospholipids were confirmed by total synthesis. Abstract : Cultivation of the extremophilic bacterium Chthonomonas calidirosea (strain T49 T ) has led to the isolation of ten compounds incorporating a phosphatidylglyceroylalkylamine core unit, eight of which have not been previously reported. The absolute regio‐ and stereochemistries of the major phospholipids were confirmed by total synthesis.